Studi Komparatif Quality of Service (QoS) pada Aplikasi Video Konferensi di Mobile Network - Faradina, Nevi; Hidayat, Rahmat; Heriawan, Rangga Agung Pribadi (Jurnal Pendidikan Teknik Elektro, 2025)
The development of 4G/5G cellular networks has accelerated the use of video conferencing applications to support online learning, business meetings, and remote collaboration. However, the performance of such services is strongly influenced by Quality of Service (QoS) parameters, namely throughput, delay, jitter, and packet loss. This study aims to analyze the QoS performance of three popular video conferencing applications, namely Zoom Meeting, Google Meet, and Microsoft Teams, when operated on two Indonesian cellular networks. The research employed a quantitative experimental approach, conducting 42-second video conferencing sessions for each application. Network traffic data were captured using Wireshark software and processed to obtain throughput, delay, jitter, and packet loss values. The results were then compared against the TIPHON standards to evaluate the service quality provided by each operator and application. The result indicates that Google Meet achieved the highest throughput on XL’s network (3307 kbps) but experienced relatively high jitter, which may reduce communication stability. Zoom recorded the lowest packet loss (0.01%) and maintained stable jitter (<20 ms), making it more reliable for real-time communication despite lower throughput. Microsoft Teams showed moderate performance but suffered from significant packet loss on Indosat’s network (2.70%). In terms of operators, XL demonstrated higher throughput, while Indosat showed more stable delay performance. In conclusion, each application exhibited different strengths: Google Meet excelled in throughput, Zoom was more consistent in minimizing jitter and packet loss, and Microsoft Teams fell in the mid-range category. These findings can serve as a reference for both end users and service providers in selecting suitable video conferencing platforms based on network conditions.